A SECURE HEALTHCARE SYSTEM FOR IOT USING ARTIFICIAL INTELLIGENCE - AL masoody , WASAN H JACOB; ALSALAMI, ABEER (Journal of Duhok University, 2023)
In recent years, healthcare facilities have been embracing technological advancements for precise patient monitoring and record management. However, ensuring the security of healthcare information and communication technology networks has emerged as a significant challenge. The use of standard algorithms to secure unstructured data, such as electronic documents and reports existing outside organized databases, has proven to be difficult. Additionally, the existing clustering methods face efficiency issues when it comes to data transfer recovery. This paper proposes the use of an Internet of Things with Artificial Intelligence System (IoT-AIS) to address healthcare security concerns. The IoT-AIS system presents a novel approach to address security concerns in healthcare systems. By combining IoT technology and machine learning algorithms, the system offers encrypted storage, individualized user access, and efficient data transmission. The simulation analysis demonstrates the system's effectiveness, highlighting its superior performance compared to existing methods. The proposed IoT-AIS system has the potential to enhance healthcare security and contribute to the advancement of IoT applications in the healthcare domain. IoT-AIS response time is consistently low, ranging from 1.1% to 6.3%. The IoT-AIS maintains a high packet delivery rate, ranging from 1.2% to 2.9%. Delay rates for IoT-AIS range from 1.2% to 6.8%. IoT-AIS consistently achieves high transmission rates, exceeding 90%. Energy usage for IoT-AIS ranges from 14.55% to 29.11% In recent years, healthcare facilities have been embracing technological advancements for precise patient monitoring and record management. However, ensuring the security of healthcare information and communication technology networks has emerged as a significant challenge. The use of standard algorithms to secure unstructured data, such as electronic documents and reports existing outside organized databases, has proven to be difficult. Additionally, the existing clustering methods face efficiency issues when it comes to data transfer recovery. This paper proposes the use of an Internet of Things with Artificial Intelligence System (IoT-AIS) to address healthcare security concerns. The IoT-AIS system presents a novel approach to address security concerns in healthcare systems. By combining IoT technology and machine learning algorithms, the system offers encrypted storage, individualized user access, and efficient data transmission. The simulation analysis demonstrates the system's effectiveness, highlighting its superior performance compared to existing methods. The proposed IoT-AIS system has the potential to enhance healthcare security and contribute to the advancement of IoT applications in the healthcare domain. IoT-AIS response time is consistently low, ranging from 1.1% to 6.3%. The IoT-AIS maintains a high packet delivery rate, ranging from 1.2% to 2.9%. Delay rates for IoT-AIS range from 1.2% to 6.8%. IoT-AIS consistently achieves high transmission rates, exceeding 90%. Energy usage for IoT-AIS ranges from 14.55% to 29.11%